The Effect of Psychosocial Interventions on Gambling Disorder: A Systematic Review - Mete, Mario Viligius Primus Hangga; Susanti, Herni; Chandra, Yudi Ariesta (Jurnal Keperawatan, 2024)
Gambling is an unlawful act that has negative consequences for the life, health, and welfare of individuals, families, and communities. One of the efforts made to reduce the health impacts of gambling is by providing psychosocial interventions. This systematic review aims to examine the effect of various types of psychosocial interventions on gambling disorders. The systematic review was conducted on Clinical Key, Clinical Key for Nursing, Science Direct, ProQuest, Scopus, Sage Journal and Springer Link, Ebsco databases with searches conducted between October - December 2023. Screening articles according to inclusion criteria in the form of full-text articles, English, and published between 2012 and 2023. The initial search results obtained 4,194 articles. Then the initial screening was carried out through reading the title and abstract so that 215 articles were left to be processed to the next stage. In the next stage, the author checked the duplication of the article, so that 51 articles were obtained. In the fourth stage, the author read the full text and obtained a total of 10 articles. The results of the 10 articles reviewed found that CBT, motivational intervention, telephone counseling, and brief intervention are various types of psychotherapy that can help overcome gambling disorders. It is not clear which therapy is better among these therapies, but all therapies have their advantages and disadvantages, which are adjusted to the client's condition. Providing psychosocial interventions such as a combination of Motivational Interview Therapy, Cognitive Behavior Therapy, telephone counseling, and Brief Telephone Intervention can provide an effective solution to help individuals overcome gambling disorders and begin the journey of recovery. The use of Motivational Interviewing therapy, Cognitive Behavior Therapy, telephone counseling, and Brief Therapy can be used in clinical and community settings to treat gambling disorder problems.